Use of electronic medical records in Morelos, Mexico: Perception of health service providers. - Parada-Toro, Irene; Rosas-Castán, Irma Lilia; Rico-Alba, Israel (Horizonte Sanitario, 2022)
Objective: To evaluate the factors related to the use of the Electronic Medical Record (ECE) from the perception of medical users of health services Morelos, Mexico. Material and methods: The qualitative analysis of 22 semi-structured interviews with medical personnel, nurses, managers and administrators of a 2nd level hospital in Morelos, Mexico was carried out, taking as a reference for analysis the dimensions of regulations, operability and training in the implementation of the ECE. Results: An insufficient number of computers and trained personnel were identified to operate the ECE. When it is possible to operate the file, it is slow or presents frequent systematic failures due to the navigation networks, they depend on the central browser that provides state support to the ECE platform without a prompt resolution when there are failures, the hospital units work 24 hours and centrally. ECE operations have 8-hour hours from Monday to Friday. This increases resistance to adopting the file as a working tool. The organization contributes to the resistance by not providing sufficient and permanent technical support to face the operational failures of the ECE. Users consider that the file is safe and reliable, which would increase the possibility of using the ECE. Conclusions: The lack of resources and inefficiencies in the operation of the ECE contribute to a low and slow adoption of the file; as well as the resistance to use it. The organization helps increase resistance if training is not efficient. Lack gives you continuous and sufficient support in the technical infrastructure and human resources. Despite the limited and inefficient adoption of ECE, areas and personnel were identified where there is greater use (hospitalization and medical personnel). These could be positive learning experiences that can be used to educate the entire organization Keywords: Electronic Medical Record; Utilization